Betamethasone dipropionate compounding for cutaneous T-cell lymphoma management. Issue 1 (1st December 2016) - Trindade, Patrícia; Gelpi, Alice; Salgado, Ana; Marto, Joana; Machado, Paula; Mateus, Dinis; Gonçalves, Humberto; Sachse, M Fernanda; Gouveia, António Melo; Ribeiro, Helena
Abstract : Background: Primary cutaneous lymphomas (extranodular non-Hodgkin lymphomas) are rare (incidence 1:100 000). Mycosis fungoides is the most common cutaneous T-cell lymphoma (CTCL) subtype. Treatment options are based on the diagnosis and the stage of the disease. Skin-directed therapies are useful for the initial stages and include topical treatments such as corticosteroids. Betamethasone dipropionate (BD) is a synthetic glucocorticoid with high anti-inflammatory activity, potency and immunosuppressant effects. It is used for topical treatment of CTCL within the following dosage 0.025–0.1% (w/w). In the Portuguese market only one topical cream contains BD at 0.05% (w/w). Objectives: To develop a new and stable emulsion containing 0.1% of BD. Methods: To accomplish this aim, development, stability, in vitro release and clinical studies of a new topical water-in-oil emulsion containing BD 0.1% w/w were assessed for the topical treatment of CTCL. Results: The three batches prepared were physically, chemically and microbiologically stable over a period of 90 days. 40% of BD was released over 6 hours and evaluation of skin lesions showed a favourable clinical effect (less itching, less infiltration, fewer patches and a reduced area of plaque). Conclusions: The clinical results show the effective cutaneous improvement of skin barrier conditions during the study.